Reconceptualizing Civic Competencies: A Multiple-Case Study on Multicultural Teacher Training in Urban Junior High Schools - Ahmad Jamalong; Muhammad Sudirman; Sulha Akhmad (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2026)
This study examines how multicultural-based Civic Education training contributes to the transformation of teacher competencies in public junior high schools in Makassar City. A qualitative multiple-case study design was employed involving 28 participants from ten schools through interviews, classroom observations, and document analysis. Data were analyzed using thematic qualitative analysis involving coding, categorization, and interpretation of emerging themes. The findings show substantial improvements in pedagogical, social, and professional competencies. Teachers shifted from lecture-dominated instruction toward collaborative discussion, case-based learning, and problem-solving activities. They also demonstrated stronger sensitivity to classroom diversity, more democratic communication patterns, and greater ability to design contextual learning materials. These changes positively influenced student participation, critical engagement, and understanding of practical civic values. However, the degree of transformation varied depending on teacher readiness, school leadership support, mentoring continuity, and facility availability. The study further proposes the Sustained Multicultural Competency Transformation Model (SMCTM), which explains how multicultural teacher competencies are shaped through the interaction of institutional, cultural, and psychological factors. The study highlights that multicultural-based professional development can serve as an effective strategy for strengthening teacher competencies in pluralistic school settings. Sustainable mentoring systems, collaborative teacher communities, and adequate institutional support are required to maintain long-term impact.